Her Royal Highness Princess Maha Chakri Sirindhorn: Princess of Taxonomy and Biodiversity of Thailand - Jirapatrasilp, Parin; Sutcharit, Chirasak; Promboon, Sumonta; Panha, Somsak (Tropical Natural History, 2025)
Her Royal Highness Princess Maha Chakri Sirindhorn (hereafter HRH Princess Sirindhorn) has demonstrated a lifelong dedication to the study of nature, biodiversity, and environmental conservation. Her initiatives have made significant impacts both in Thailand and internationally. Through her leadership, numerous projects have been championed including botanical gardens, school botanical garden-based education, plant genetic conservation, seed preservation programs, organic farming, natural history museums and the Flora of Thailand project. The Princess’s contributions extend beyond institutional development to inspire and support new generations of taxonomists and biologists. Her comprehensive understanding of biodiversity, coupled with the ability to recognize both its inherent beauty and practical applications, has guided her approach to sustainable development. Moreover, her work exemplifies how scientific knowledge can be applied for the benefit of humanity while preserving natural heritage. Through her decades-long commitment to this field, HRH Princess Sirindhorn serves as a powerful role model, inspiring children and youth to develop their own appreciation for nature and commitment to environmental conservation.